Channel Capacity Improvement of MIMO Communication Systems using Different Techniques - Shahir Fleyeh Nawaf (Tikrit Journal of Engineering Sciences, 2018)
The modern communication systems require high data, and this rate cannot be achieved in Single input- Single out put (SISO) systems. This prosperity can be gained by improving the channel capacity using systems for Multiple Input-Multiple output (MIMO). In this paper the parameters effecting channel capacity are studied, these include (antennas numbers, antennas distribution, and Signal to Noise Ratio (SNR)) using multiplexing, diversity and beamforming techniques. The results showed that the channel capacity for multiplexing technique increased semi-linearly with antennas number when the antennas at transmitter side and receiver side are equal. While the increase in capacity became less when the antennas distribution is different. Increasing the antennas ate the receiver side gives better capacity than increasing the antennas ate the transmitter side. The multiplexing techniques give the best performance from diversity techniques and beamforming when (SNR) greater than (10 dB). While the beamforming technique gives the best performance for (SNR) less than (10 dB).